2003
DOI: 10.1016/s0014-5793(03)01164-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis of Campylobacter jejuni using whole genome DNA microarrays

Abstract: Whole genome DNA microarrays were constructed and used to investigate genomic diversity in 18 Campylobacter jejuni strains from diverse sources. New algorithms were developed that dynamically determine the boundary between the conserved and variable genes. Seven hypervariable plasticity regions (PR) were identi¢ed in the genome (PR1 to PR7) containing 136 genes (50%) of the variable gene pool. When comparisons were made with the sequenced strain NCTC11168, the number of absent or divergent genes ranged from 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
134
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 40 publications
12
134
1
Order By: Relevance
“…Using the association mapping method described here, we have shown that one factor driving rapid host adaptation is gain and loss of the panBCD genes encoding the vitamin B 5 biosynthesis pathway, which has already been highlighted as especially variable in a previous study (13). Vitamin B 5 is abundant in cereals and grains but is found in a very low concentration in grasses (14), which, respectively, constitute the main diets of chicken and cattle.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Using the association mapping method described here, we have shown that one factor driving rapid host adaptation is gain and loss of the panBCD genes encoding the vitamin B 5 biosynthesis pathway, which has already been highlighted as especially variable in a previous study (13). Vitamin B 5 is abundant in cereals and grains but is found in a very low concentration in grasses (14), which, respectively, constitute the main diets of chicken and cattle.…”
Section: Discussionmentioning
confidence: 77%
“…Host-associated genomic regions. (A) Distribution of 10 locations containing 8,538 host-associated words for which homologs were found in reference genome NCTC11168, visualized using Artemis (12) and DNAPlotter (13). The red lines indicate host-associated words, the cyan rings show the protein coding sequences on the forward and reverse strands, and the green rings indicate other annotated features using default settings.…”
Section: Bmentioning
confidence: 99%
“…Comparative genomic hybridizations (CGHs) by DNA micro-and macroarrays have been employed to reveal the evolution and function of pathogenicity in genomic terms in organisms such as Escherichia coli (Dobrindt et al, 2003;Carter et al, 2008), Yersinia pestis (Hinchliffe et al, 2003), Yersinia pseudotuberculosis (Zhou et al, 2004), Xylella fastidiosa (Koide et al, 2004), Campylobacter jejuni (Pearson et al, 2003), Streptococcus agalactiae (Brochet et al, 2006) and Streptococcus pneumoniae (Obert et al, 2006). The results of these studies indicate that mobile genetic elements such as phages, transposons and GIs contribute to pathogenicity acquisition and environmental adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…These include the cytolethal distending toxin, the flagellar structural proteins, the PEB antigenic surface proteins, and the general protein glycosylation locus (10). In another study, the genomic diversity of 18 C. jejuni strains from diverse sources was investigated (12). Seven hypervariable plasticity regions (PRs) were identified in the genome (PR1 to PR7).…”
mentioning
confidence: 99%
“…In this particular study, algorithms were used that selected a dynamic boundary between the conserved and variable genes similar to the GACK algorithm (13). More recently, genomic comparisons of 51 strains isolated from food and clinical sources have been integrated with data from the three previous C. jejuni DNA microarray studies (10)(11)(12) to perform a metaanalysis that included 97 strains from the four separate data sets (14). In that study (14), a large proportion of the variable genes were found to be absent or divergent in single strains only, and these uniquely variable genes could be mapped to previously defined variable loci.…”
mentioning
confidence: 99%